PENGARUH PERTUMBUHAN PERUSAHAAN, KEBIJAKAN DEVIDEN, DAN STRUKTUR MODAL TERHADAP KINERJA KEUANGAN - SHAFIRA REFIANA, DIAN; Suharna (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2024)
Financial performance is very important for companies to find out the extent to which the company has implementend it properly and correctly, so it is used by management in making financial decisions, especially profitability conditions, capital adequacy and liquidity conditions. This research aims to determine and provide empirical evidence or the influence of company growth, dividend policy, and capital structure on financial performance in non-cyclical consumer companies in the food and beverage sector to the 2018-2022 period. This researvh method is quantitative using secondary data obtained from the Indonesian Stock Exchange (IDX) and on the official website of each company with purposive sampling and the final sampel obtained was 18 companies and the total number of observation data was 90 data. The data analysis technique uses panel data regression analysis with the help of the EViews 12 program. The results of this research show that partially company growth, dividend policy, and capital structure have a significant effect on financial performance